2010
DOI: 10.1097/eja.0b013e328331a37b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of articaine and ropivacaine on calcium handling and contractility in canine ventricular myocardium

Abstract: Under conditions of normal application both articaine and ropivacaine are free of cardiodepressant effects; however, a negative inotropic action can be anticipated in cases of accidental intravenous injection or overdose. The observed negative inotropic actions of articaine and ropivacaine are similar in magnitude, and can be mainly attributed to a reduction in net trans-sarcolemmal Ca influx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Besides sarcoplasmic reticulum calcium release, sarcoplasmic reticulum calcium reuptake was blockade and calcium sensitivity of the contractile system was increased with racemic bupivacaine and its isomers, displaying a stereoselectivity to S(-)bupivacaine and leading to myocardial relaxation slowness 7,14 . It was also demonstrated high ropivacaine concentrations caused L-type calcium channel blockade, leading to negative inotropic effects in canine ventricular muscle 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides sarcoplasmic reticulum calcium release, sarcoplasmic reticulum calcium reuptake was blockade and calcium sensitivity of the contractile system was increased with racemic bupivacaine and its isomers, displaying a stereoselectivity to S(-)bupivacaine and leading to myocardial relaxation slowness 7,14 . It was also demonstrated high ropivacaine concentrations caused L-type calcium channel blockade, leading to negative inotropic effects in canine ventricular muscle 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated negative inotropic effects with different LA 8,[13][14][15] . Divergent LA concentrations were described to induce myocardial contractile function impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Articaine can modify cardiac action potentials and ion currents at concentrations higher than the therapeutic range, but may be moderate even in the case of overdose 75. The effects of articaine and ropivacaine on the components of intracellular Ca 2+ handling, the cause of negative inotropic actions, were studied and compared in canine ventricular myocardium 76. Under conditions of normal application, both articaine and ropivacaine are free of cardiodepressant effects.…”
Section: Toxicity and Safetymentioning
confidence: 99%
“…end-product inhibition). LSR was obtained as described above from rabbit skeletal muscle and the protein concentration was 5.5 g/ml in each experiment [22]. Total hydrolytic activity was measured as the decrease of optical density at the NADH absorbance wavelength (340 nm) and expressed in micromoles of inorganic phosphate per milligrams of protein per minute (abbreviated as I.U.)…”
Section: Atpase Activity Measurementsmentioning
confidence: 99%